Experimental unit for determining body weight of astronauts and light-weight objects in zero-gravity conditions - Kolomiitsev, Oleksii; Komarov, Volodymyr; Dmitriiev, Oleh; Pustovarov, Volodymyr Volodymyrovich; Oliinyk, Ruslan (Національний технічний університет "Харківський політехнічний інститут", 2022)
The transition of an astronaut into zero gravity leads to a certain restructuring of the body, including the redistribution of fluid flows in it. The process of dehydration of the body is stimulated, the astronaut loses weight. Knowledge of the regularities of changes in an astronaut's body weight, keeping it within normal limits thanks to a rational load distribution, rest, physical exercises, and a well-thought-out diet are extremely necessary in order to provide the astronaut with the most favorable conditions for adaptation in zero gravity, as well as to better prepare him for his return to Earth. Returning materials for scientific research and experiments, as well as equipment, from the space station to Earth also requires high-precision determination of the low weight of objects. The object of the research is an experimental unit that allows measuring the weight (parameters) of the astronaut’s body and the small weight of objects (equipment, devices, etc.) that oscillate. The subject of research is the frequency of natural oscillations of the dynamic system. The purpose of scientific work is the development of an experimental unit for determining the weight of the astronaut’s body and the low weight of objects in zero gravity. Conclusions. An experimental setup for determining the body weight of astronauts and the low weight of objects (control objects – СО) in zero gravity is proposed. For high-precision determination of the weight of the СО in zero gravity, the natural frequency (NF) was chosen as a diagnostic parameter. In the experimental installation, the weight of the OC is determined by changing the NF of the dynamic system "control object – moving anchor" depending on the attached weight of the СO. The essence of the work of the experimental unit is revealed, and its general appearance and structural scheme are presented.

Перехід космонавта у невагомість призводить до певної перебудови організму, у тому числі до перерозподілу у ньому потоків рідини. Стимулюється процес обезводнення організму, космонавт втрачає у вазі. Знання закономірностей змін ваги тіла космонавта, збереження її в нормальних межах завдяки раціональному, розподілу навантаження, відпочинку, фізичних вправ, продуманому режиму харчування украй необхідно, щоб забезпечити космонавту найбільш сприятливі умови для адаптації у невагомості, а також краще підготувати його до повернення на Землю. Повернення з космічної станції на Землю матеріалів наукових досліджень і експериментів, а також обладнання також потребує високоточного визначення малої ваги об'єктів. Об'єктом дослідження є експериментальна установка, що дозволяє вимірювати вагу (параметри) тіла космонавта і малу вагу об'єктів (обладнання, пристроїв тощо), що коливаються. Предметом дослідження є частота власних коливань динамічної системи. Метою наукової роботи є розробка експериментальної установки для визначення ваги тіла космонавта та малої ваги об’єктів в умовах невагомості. Висновки. Запропоновано експериментальну установку для визначення ваги тіла космонавтів (астронавтів) та малої ваги об'єктів (об'єктів контролю (ОК)) в умовах невагомості. Для високоточного визначення ваги ОК в умовах невагомості у якості діагностичного параметра обрана частота власних коливань (ЧВК). В експериментальній установці визначення ваги ОК здійснюється за зміною ЧВК динамічної системи "об'єкт контролю – рухомий якір" залежно від приєднаної ваги ОК. Розкрито сутність роботи експериментальної установки та представлено її загальний вигляд і структурна схема.
Експериментальна установка для визначення ваги тіла космонавта та малої ваги об'єктів в умовах невагомості
Keywords: zero gravity; astronaut's body weight; ow weight of objectsl; object control; experimental setup; natural frequency; dynamic system; невагомість; вага тіла космонавта; мала вага об'єктів; об'єкт контролю; експериментальна установка; частота власних коливань; динамічна система